Responsible innovation: exploring how Malaysia small-medium enterprises (SMEs) co-create value with external stakeholders in different industries - Chuah, Catherine Jia Qian (2023)
It is said that a sustainable business model can responsibly innovate to affect society, the environment, and the economy. Several scholars are interested in co-creation, one of the facets of responsible innovation. There is now a wealth of literature examining the many forms of co-creation as well as the benefits and effects of doing so in a business-to-consumer setting. Research on how SMEs collaborate with outside parties to accomplish responsible innovation in the context of B2C and B2B, however, is woefully inadequate, particularly in Malaysia. This study fills that gap.